2018
DOI: 10.1155/2018/4595130
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel from “Morelos” Rice: Synthesis, Oxidative Stability, and Corrosivity

Abstract: Rice bran is a by-product of great production worldwide and its use for the synthesis of biodiesel does not affect the food chain and therefore it is an excellent alternative for the production of biofuels with low carbon footprint. In this work, the synthesis of biodiesel was carried out from the raw rice bran oil of a kernel variety called “Morelos rice.” The stability and corrosivity characteristics of biodiesel were determined. Biodiesel stability was determined both under storage conditions and under acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Biodiesel represents a viable fuel substitute to reduce the pollutant emissions produced by the combustion of diesel derived from oil in compression-ignition engines. It has several advantages as compared to diesel fuel oil such as its sustainability, its ability to maintain the balance of the carbon cycle, it is biodegradable, it has a level of lubrication, and it reduces the emission of toxic pollutants that are harmful to human health [2,3]. Nevertheless, its main disadvantage is the high cost of refined oils used as feedstock for its production, which can represent between 60% and 80% of the final cost of biodiesel production.…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel represents a viable fuel substitute to reduce the pollutant emissions produced by the combustion of diesel derived from oil in compression-ignition engines. It has several advantages as compared to diesel fuel oil such as its sustainability, its ability to maintain the balance of the carbon cycle, it is biodegradable, it has a level of lubrication, and it reduces the emission of toxic pollutants that are harmful to human health [2,3]. Nevertheless, its main disadvantage is the high cost of refined oils used as feedstock for its production, which can represent between 60% and 80% of the final cost of biodiesel production.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of residual oil without the catalyst, this band was smaller. It has been indicated that its presence may correspond to the alcohol group (OH), oxydryl (OH–), or hydrogen bonding [11,45]. The presence of this signal can be associated with the alcohol groups of the glycerol, that is, mono- and diacylglycerides are present in the oil due to the incomplete transesterification of the triacylglycerides.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 16 shows the FTIR spectra of the biodiesel synthesized in the presence and absence of the catalyst at 200 °C for 6 h. Due to the structural similarity that exists between triglycerides and methyl esters, the spectra of both are similar [11]. In the spectra, the characteristic peak of the carbonyl group of the methoxyesters (–CO–OCH 3 ) was observed at ≈1743 cm −1 , which has been used to confirm the conversion of the oil to biodiesel [45,46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platinum wires were used as the reference and counter electrodes. Previous work has reported using platinum as a reference electrode in electrochemical measurements and shown that using platinum as a reference electrode instead of conventional electrodes does not alter the information's content [32][33][34][35]. The working electrode was an aluminum-made plate (reaction area ~1 cm 2 ), to which a copper conductor wire was welded on one of its faces, followed by encapsulation in epoxy resin.…”
Section: Electrochemical Assaysmentioning
confidence: 99%